Immune response of healthy adults to the ingested probiotic Lactobacillus casei Shirota - Harbige, Laurence S.; Pinto, E.; Allgrove, J.; Thomas, L. V. (Wiley, 2016)
Daily ingestion of a probiotic drink containing Lactobacillus casei Shirota (LcS; 1.3 9 1010 live cells) by healthy adults for (1) 4-week LcS, (2) 6-week discontinuation of LcS and (3) a final 4 weeks of LcS was investigated. There was a significant increase in expression of the T cell activation marker CD3+CD69+ in ex vivo unstimulated blood cells at weeks 10 and 14, and there was a significant increase in the NK cell marker CD3+CD16/56+ in ex vivo unstimulated blood cells at weeks 4, 10 and 14. Expression of the NK cell activation marker CD16/56+CD69+ in ex vivo unstimulated blood cells was 62% higher at week 10 and 74% higher at week 14. Intracellular staining of IL-4 in ex vivo unstimulated and PMA-/ionomycin-stimulated CD3+ b7+ integrin blood cells was significantly lower at weeks 10 and 14. Intracellular staining of IL-12 in ex vivo unstimulated and LPS-stimulated CD14+ blood cells was significantly lower at weeks 4, 10 and 14. Intracellular staining of TNF-a in LPS-stimulated CD14+ blood cells was significantly lower at weeks 4, 10 and 14. Mucosal salivary IFN-c, IgA1 and IgA2 concentrations were significantly higher at week 14, but LcS did not affect systemic circulating influenza A-specific IgA or IgG and tetanus-specific IgG antibody levels. In addition to the decrease in CD3+b7+ integrin cell IL-4 and a reduced CD14+ cell pro-inflammatory cytokine profile, at week 14 increased expression of activation markers on circulating T cells and NK cells and higher mucosal salivary IgA1 and IgA2 concentration indicated a secondary boosting effect of LcS.